Downsizing Prisons in an Age of Austerity?: Justice Reinvestment and Women’s Imprisonment - Stubbs, Julie (Oñati Socio-Legal Series, 2016)
Justice Reinvestment is being actively promoted as one means of reducing high levels of incarceration through diverting expenditures from prisons to fund services intended to provide support and supervision for offenders within the community and to prevent crime. At a time of financial stringency, the huge expenditure necessitated by high incarceration rates is being re-examined. There is growing recognition that high levels of incarceration are ineffective in reducing recidivism and may be criminogenic and damaging in other ways for individuals and communities. Based on claims that Justice Reinvestment schemes in the US have produced promising results, some activists and politicians in Australia have urged the adoption of Justice Reinvestment. This advocacy has emphasised the need to find mechanisms to reduce the very high levels of incarceration of Indigenous people. Women’s imprisonment rates have increased substantially in recent years and to a greater extent than rates for men. This pattern has been observed in several jurisdictions and is even more pronounced for Indigenous women. This paper critically examines features of Justice Reinvestment, such as its endorsement of ‘evidence based policy’ and risk assessment tools, to question whether these features are likely to promote the interests of women.